Analysis of the D-dimer/Platelets Ratio in Sepsis Patients at Dr. Wahidin Sudirohusodo Hospital Makassar - Yarianti Yarianti; Darwati Muhadi; Agus Alim Abdullah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Sepsis is a condition with a life-threatening organ dysfunction. This condition is caused by a dysregulated host response to infection. This study aimed to determine the ratio and cut-off value of D-dimer/platelets in sepsis patients. This study was a cross-sectional observational study. This study took secondary data from the medical records of 142 patients at Dr. Wahidin Sudirohusodo Hospital (RSWS) from January 2018 to December 2021. The results of this study showed that the D-dimer/platelet ratio was significantly higher in those who died (mean 0.151) compared to those who survived (mean 0.028) (p<0.015) with a cut-off value of 0.020.